Una propuesta para estudiar la complejidad de los programas de formación de profesores de matemáticas - Gil Chaves, Diana (Revista Científica, 2019)
This article presents the design of the structure of the system for the study of the mathematics teacher training program, as one of the results of the development of the research. The central purpose of the research consisted of the design and application of a system of relations between the fields: teacher training in mathematics, curriculum, and mathematics teaching. This system of relationships was built from the study of three aspects within each of the fields. The first aspect, the study of the senses and possible meanings (conceptual subfield) of: the training of teachers of mathematics, the curriculum for the training of teachers and the didactics of mathematics. The second aspect, the study of the intellectuals that organizes the productions of other intellectuals (intellectual subfield) in each of the three fields. And the third aspect, the study of the problems and the decision-making process (decisional subfield) in the training programs, especially the situations in which one of the three fields is referred to. The conclusions are focused on the design of characterizing and differentiating tools that allow the study of mathematics teacher training programs from three fields present and necessary for the existence of any mathematics teacher training program.